2018
DOI: 10.14295/aimj.v3i5.50
|View full text |Cite
|
Sign up to set email alerts
|

Simulatiom Based Education as Tool in Emergency Medicine: A Systematic Review

Abstract: INTRODUCTION: Realistic simulation is increasingly present in academic curricula. The traditional method of teaching is being gradually replaced by new methodological approaches, which reliably reproduce real situations and produce technical knowledge and skills in medical students in the medical emergency.Realistic simulation is increasingly present in the academic curriculum. The traditional method of teaching is being gradually replaced by new methodological approaches, which reliably reproduce real situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported the use of digital games as a tool for active teaching and learning in health education (Andrews et al, 1992; Ellis & Hannigan, 1986; Payne & Rowberg, 1984). Since then, new digital games termed “serious” have been developed and utilized by students and health care professionals in the areas of Nursing, Pharmacy, and Medicine (Bernardo et al, 2018; Boada et al, 2018; Gallegos et al, 2017; Kleinert et al, 2015; Lam et al, 2019; Lee et al, 2018; Malhotra et al, 2017; Sera & Wheeler, 2017; Verkuyl et al, 2016). Serious games are games that are used in the teaching-learning processes or training, with the main purpose being to educate rather than to entertain (Baptista & Oliveira, 2018; Fonseca et al, 2014; Rodriguez et al, 2014; Serrano-Laguna et al, 2017; Tandogan & Orhan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the use of digital games as a tool for active teaching and learning in health education (Andrews et al, 1992; Ellis & Hannigan, 1986; Payne & Rowberg, 1984). Since then, new digital games termed “serious” have been developed and utilized by students and health care professionals in the areas of Nursing, Pharmacy, and Medicine (Bernardo et al, 2018; Boada et al, 2018; Gallegos et al, 2017; Kleinert et al, 2015; Lam et al, 2019; Lee et al, 2018; Malhotra et al, 2017; Sera & Wheeler, 2017; Verkuyl et al, 2016). Serious games are games that are used in the teaching-learning processes or training, with the main purpose being to educate rather than to entertain (Baptista & Oliveira, 2018; Fonseca et al, 2014; Rodriguez et al, 2014; Serrano-Laguna et al, 2017; Tandogan & Orhan, 2007).…”
Section: Introductionmentioning
confidence: 99%